Orthodontic-Surgical Management of Class III Malocclusion with Mandibular Asymmetry: A Case Report - eka setyawardana; Wanda Karisma Dian Sari; Windy Yuliartanti (Cakradonya Dental Journal, 2026)
Skeletal Class III malocclusion is a complex dentofacial deformity with multifactorial etiology, most commonly associated with maxillary deficiency. This skeletal discrepancy may negatively affect facial esthetics and is frequently accompanied by pronounced facial asymmetry. In moderate to severe cases, particularly after growth completion, definitive correction typically requires a combination of orthodontic treatment and orthognathic surgery to achieve functional occlusion and improve facial harmony. This case report describes the treatment of a 16-year-old patient with skeletal Class III malocclusion characterized by transverse maxillary constriction, unilateral posterior open bite on the left side, anterior crossbite, and unilateral posterior crossbite. The patient also presented significant negative dentoalveolar discrepancy in the maxillary arch. Extraoral examination revealed maxillary hypoplasia, increased lower anterior facial height, a concave facial profile, and facial asymmetry with mandibular deviation to the left. Treatment was performed in three sequential phases: presurgical orthodontic decompensation, orthognathic surgery to correct the skeletal discrepancy, and postsurgical orthodontic finishing. The patient demonstrated stable intercuspation, satisfactory masticatory efficiency, and marked improvement in facial symmetry and profile. These findings indicate that an integrated orthodontic–surgical approach can effectively address both functional and esthetic concerns in patients with skeletal Class III malocclusion accompanied by facial asymmetry.